2011
DOI: 10.1371/journal.pone.0018286
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Signatures of Bladder Cancer Revealed by Deep Sequencing

Abstract: BackgroundMicroRNAs (miRNAs) are a class of small noncoding RNAs that regulate gene expression. They are aberrantly expressed in many types of cancers. In this study, we determined the genome-wide miRNA profiles in bladder urothelial carcinoma by deep sequencing.Methodology/Principal FindingsWe detected 656 differentially expressed known human miRNAs and miRNA antisense sequences (miRNA*s) in nine bladder urothelial carcinoma patients by deep sequencing. Many miRNAs and miRNA*s were significantly upregulated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
194
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(236 citation statements)
references
References 31 publications
35
194
2
4
Order By: Relevance
“…In the present study, it was found that miR-195 expression was significantly downregulated in bladder cancer tissues compared with that in their matched normal adjacent tissues, which was consistent with other studies (4,17). The first finding that miR-195 expression was notably downregulated in bladder cancer tissues when compared with that in normal bladder epithelium tissues was reported in a study by Ichimi et al (4).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, it was found that miR-195 expression was significantly downregulated in bladder cancer tissues compared with that in their matched normal adjacent tissues, which was consistent with other studies (4,17). The first finding that miR-195 expression was notably downregulated in bladder cancer tissues when compared with that in normal bladder epithelium tissues was reported in a study by Ichimi et al (4).…”
supporting
confidence: 92%
“…The first finding that miR-195 expression was notably downregulated in bladder cancer tissues when compared with that in normal bladder epithelium tissues was reported in a study by Ichimi et al (4). Han et al (17) then examined the expression profile of miRNAs using deep sequencing and qPCR, and showed that miR-195 expression was notably downregulated in bladder cancer tissues compared with that in matched histologically normal urothelium. More recently, Itesako et al (18) examined the miRNA expression signature of bladder cancer by deep sequencing, and revealed the functional significance of the miR-195/497 cluster.…”
mentioning
confidence: 99%
“…These miRNAs regulate gene expression by targeting the 3' untranslated regions (3'UTRs) of mRNAs (1)(2)(3)(4)(5)(6). Numerous studies have shown that miRNAs act as intrinsic regulators of many cellular processes, including cell proliferation, apoptosis, invasion and differentiation (7)(8)(9)(10)(11)(12). Aberrant expression of miRNAs has been found to be associated with the development and progression of numerous types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…37 Importantly, supporting evidence from recent deep sequencing studies do not report an expression for c-miRCh9 among the identified microRNA expression signatures of bladder cancer. 40 Computational identification of a highly significant and evolutionary conserved target binding site for this potential miRNA in the CCND2 oncogene using Targetprofiler was the initial incentive for performing reporter gene assays. CCND2 is a well known cyclin which functions in the cell mut-3'UTR).…”
Section: Resultsmentioning
confidence: 99%